2023
DOI: 10.3389/fnint.2022.1054627
|View full text |Cite|
|
Sign up to set email alerts
|

High levels of Bifidobacteriaceae are associated with the pathogenesis of Parkinson’s disease

Abstract: BackgroundThe diagnosis of Parkinson’s disease (PD) is complex and there are no biomarkers for early identification. Many studies have reported altered gut microbiota in patients with PD compared with healthy individuals. However, results from previous studies vary across countries.AimsThe aim of this study was to identify gut microbiota biomarkers that could be used as a marker for the diagnosis of PD.MethodsFirstly, the differential gut microbiota was obtained by meta-analysis, and then the results of meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Thus, the enrichment of the above flora in the lungs suggests that lung transplant patients may be comorbid with severe PGD. Similarly, intestinal Scardovia wiggsiae has been reported as a new potential biomarker for the diagnosis of Parkinson's disease 21 . There are no studies illustrating the association of the above flora with lung disease and our findings provide evidence for the relevance of these flora to lung disease.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Thus, the enrichment of the above flora in the lungs suggests that lung transplant patients may be comorbid with severe PGD. Similarly, intestinal Scardovia wiggsiae has been reported as a new potential biomarker for the diagnosis of Parkinson's disease 21 . There are no studies illustrating the association of the above flora with lung disease and our findings provide evidence for the relevance of these flora to lung disease.…”
Section: Discussionmentioning
confidence: 47%
“…This study provides insight into the composition of the lung microbiota in patients with severe PGD, how the lung microbiota interacts with the immune system, and reveals the molecular and cellular mechanisms 21 There are no studies illustrating the association of the above flora with lung disease and our findings provide evidence for the relevance of these flora to lung disease. In some lung transplant patients, reflux is associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 75%
“…Bifidobacteriaceae are a family of bacteria with fermentative metabolism that inhabit the gastrointestinal tract of humans and animals [43]. A previous meta-analysis suggested that high populations of Bifidobacteriaceae may be involved in the pathogenesis of Parkinson's disease [44], while a systematic review indicated a higher abundance of Bifidobacteriaceae in individuals with depression [45]. Our results showed a decrease in the relative abundance of Bifidobacteriaceae in male rats when compared with female rats.…”
Section: Discussionmentioning
confidence: 49%
“…While numerous studies identify B. dentium as a probiotic flora, other reports speculate that it may contribute to gait issues in PD via this microbe’s ability to convert glutamate to GABA 70 , as elevated GABA levels in one study have been associated with a worsened PD gait 71 . Previous reports in PD patients have implicated overactive glutamate receptors in the promotion of neurodegeneration 72 as well as identified increased glutamate degradation and low glutamate production in the PD gut metagenome 73 .…”
Section: Discussionmentioning
confidence: 98%